2011
DOI: 10.1016/j.procs.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous feature selection and ant colony clustering

Abstract: Clustering is a widely studied problem in data mining. Ai techniques, evolutionary techniques and optimization techniques are applied to this field. In this study, a novel hybrid modeling approach proposed for clustering and feature selection. Ant colony clustering technique is used to segment breast cancer data set. To remove irrelevant or redundant features from data set for clustering Sequential Backward Search feature selection technique is applied. Feature selection and clustering algorithms are incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Several ACO based feature selection algorithms have been proposed for the UCI dataset. The authors of [ 22 26 , 28 , 29 , 31 , 33 , 34 ] have reported that their proposed ACO based algorithms increase the performance of classification. According to our experimental results, we also observed that ACO based feature selection algorithm improves the classification performance in terms of classification accuracy and time for the WebKB and Conference datasets in general.…”
Section: Experimental Evaluation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ACO based feature selection algorithms have been proposed for the UCI dataset. The authors of [ 22 26 , 28 , 29 , 31 , 33 , 34 ] have reported that their proposed ACO based algorithms increase the performance of classification. According to our experimental results, we also observed that ACO based feature selection algorithm improves the classification performance in terms of classification accuracy and time for the WebKB and Conference datasets in general.…”
Section: Experimental Evaluation and Resultsmentioning
confidence: 99%
“…Akarsu and Karahoca [ 29 ] have used ACO for clustering and feature selection. Ant colony clustering technique is used to segment breast cancer dataset.…”
Section: Related Workmentioning
confidence: 99%
“…One is setting the current value of pheromone to the initial value once every 50 iterations while the other is setting the pheromones on all paths to the initial value if the pheromones on the paths remain intact for the past 10 iterations in a row. Akarsu and Karahoca [28] used sequential backward selection (SBS) to reduce the dimensions of patterns. They use Manhattan distance as the fitness function and consider the pheromone only when the ants select paths.…”
Section: Ant Colony Optimization Formentioning
confidence: 99%
“…Then, in the local pheromone update phase, the positive pheromone values will be updated, as lines (18)- (21) show. Finally, in the global pheromone update phase, the best and worst ants will be found and the positive and negative pheromone values on the paths they passed through will be updated, as lines (23)- (28) depict. Once the termination criterion is met, MPTACO will output the best result (line (30)) and terminate the search process.…”
Section: Pseudocode Of Mptacomentioning
confidence: 99%